2007
DOI: 10.1163/156939307783152795
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Dielectric Resonator Antenna by Applying a Combined Semi-Analytical Method and Simulation

Abstract: The radiation properties of a hemispherical dielectric resonator, consisting of a monopole antenna placed in a dielectric hemisphere is theoretically examined. A method based on the combination of Green's function theory, in conjunction with the Method of Auxiliary Sources (MAS), is used to solve analytically and calculate the electromagnetic field at any arbitrary point of the structure. The Green's function theory is used to calculate the response of the hemisphere to an excitation consisting of an elementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The real part is obtained by evaluating the integral given by (33) for k 2 x + k 2 y ≤ k 2 ,and the imaginary part by evaluating the integral for k 2 x + k 2 y ≥ k 2 . These two regions correspond to the visible region (radiation field) and the invisible region (evanescent field) respectively.…”
Section: Evalauation Slot Electric Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The real part is obtained by evaluating the integral given by (33) for k 2 x + k 2 y ≤ k 2 ,and the imaginary part by evaluating the integral for k 2 x + k 2 y ≥ k 2 . These two regions correspond to the visible region (radiation field) and the invisible region (evanescent field) respectively.…”
Section: Evalauation Slot Electric Fieldmentioning
confidence: 99%
“…It has been shown that dielectric resonator antennas (DRA) can be used as effective radiators at microwave frequencies where ohmic losses become a serious problem for conventional metallic antennas [1][2][3][4]. DRAs offer several advantages such as small size, low cost, light weight, ease of excitation and ease of integration with active circuitry.…”
Section: Introductionmentioning
confidence: 99%
“…However, the introduction of the inner GMRES method also consumes much computational costs. And the overall convergence improvement depends on the balance of the acceleration effect and the added computational cost [19][20][21][22][23][24][25][26][27][28].…”
Section: Gmres-ir Dgmres Fgmres Gmresrmentioning
confidence: 99%
“…Another MOM numerical study of split cylindrical dielectric resonator antennas on a conducting ground plane excited by a coaxial probe with a bandwidth of 35% is previously presented in [12]. In addition, the other analytical simulations on the various DRAs were presented in [13,14]. In these studies, not only, the analyses on the DRA with multiband operation have been not done, but also, the majority of the used dielectrics have low permittivity which simplifies the design.…”
Section: Introductionmentioning
confidence: 99%